Copper(II)-Catalyzed β-Borylation of Acetylenic Esters in Water - Peck, Cheryl L.; Calderone, Joseph A.; Santos, Webster L. (Synthesis, 2015)
A method for the β-borylation of alkynoates has been developed. In the presence of bis(pinacolato)diboron and catalytic amounts of both copper(II) and 4-picoline, substituted alkynoates undergo borylation in a regio-, stereo-, and chemoselective fashion. The reaction is performed under mild conditions using water as solvent and open to the atmosphere to exclusively afford (Z)-β-boryl-α,β-unsaturated esters.
Keywords: boron; copper; stereoselectivity; hydroboration; alkynes